Rozvoj obchodních aktivit firmy prostřednictvím franchisingu - Pavlík, Jakub (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Diplomová práce pojednává o rozvoji obchodních aktivit vybraného subjektu prostřednictvím franchisingového podnikání. Předmětem práce je definování teoretických východisek z oblasti franchisingu, provedení analýzy současného stavu společnosti AQUAdesign s.r.o. a vytvoření návrhu franchisingového konceptu dané společnosti. Návrhová část práce je poté doplněna o příslušný harmonogram implementace.

The master´s thesis deals the development of the business activity selected subject through franchising. The main subject of this thesis is theoretical basis of the definition of the Franchising, to execute an analysis of the current state of AQUAdesign s.r.o. and to suggest concept of franchising the company. The last part of this thesis is timetable of implementation.
Business Development of Company Through Franchising
Keywords: franchising; franchisor; franchisant; franchisingová smlouva; analýza SLEPT; Porterova analýza; analýza 7S; manuál; franchising; franchisor; franchisant; franchising contract; SLEPT analysis; Porter analysis; 7S analysis; manual